2008
DOI: 10.1534/genetics.108.091330
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Evolutionary Adaptation by Escherichia coli to Stressful Cycles of Freezing, Thawing and Growth

Abstract: Microbial evolution experiments offer a powerful approach for coupling changes in complex phenotypes, including fitness and its components, with specific mutations. Here we investigate mutations substituted in 15 lines of Escherichia coli that evolved for 1000 generations under freeze-thaw-growth (FTG) conditions. To investigate the genetic basis of their improvements, we screened many of the lines for mutations involving insertion sequence (IS) elements and identified two genes where multiple lines had simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 80 publications
0
27
0
Order By: Relevance
“…As E. coli enters stationary phase, the enzyme cardiolipin synthase catalyzes the conversion of phosphatidylglycerol to cardiolipin. Mutations in cls increase membrane fluidity (45) and contribute to increased survival after repeated cycles of freezing and thawing (52); however, the cls mutation had no effect on pressure resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As E. coli enters stationary phase, the enzyme cardiolipin synthase catalyzes the conversion of phosphatidylglycerol to cardiolipin. Mutations in cls increase membrane fluidity (45) and contribute to increased survival after repeated cycles of freezing and thawing (52); however, the cls mutation had no effect on pressure resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our results and those of Malone et al (35) suggest that the cold-shock response may contribute to enhanced pressure resistance. UspB (universal stress protein B) is believed to be a membrane protein under RpoS regulation that confers resistance to ethanol and freeze-thaw stress (15,52). The mean differential survival ratio of the uspB mutant, although similar to that of cspA, was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli is often used to study bacterial adaptation (49), experimental evolution (9,36), and speciation (11,28,33,43). Comparisons between representative genomes continue to provide valuable information about these processes (58), and as genetic data accumulate, our understanding of how bacteria adapt to change and evolve is clarified.…”
mentioning
confidence: 99%
“…As such, our data underscore that, aside from absolute resistance, resuscitation speed itself is an evolvable trait. Previous work showed that E. coli can also improve its resuscitation time in response to recurring freeze-thaw cycles (32,33), suggesting that selection for faster recovery is a more general phenomenon that can be triggered by several stresses. Interestingly, most recent evidence seems to suggest that E. coli can evolve to increase the time it needs or takes before growth resumption to avoid being killed by antibiotics (34).…”
Section: Discussionmentioning
confidence: 99%